Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445701
|View full text |Cite
|
Sign up to set email alerts
|

You’re Making Me Sick

Abstract: While multiple studies suggest that female-identified participants are more likely to experience cybersickness in virtual reality (VR), our systematic review of 71 eligible VR publications (59 studies and 12 surveys) pertaining to gender and cybersickness reveals a number of confounding factors in study design (e.g., a variety of technical specifications, tasks, content), a lack of demographic data, and a bias in participant recruitment. Our review shows an ongoing need within VR research to more consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…In future work, we will explore commercial asymmetric VR games as well. Additionally, limitations of our thematic findings are bound to the limitations of the reviewed papers-for example, as also found in general VR research (Peck et al, 2020;MacArthur et al, 2021), this subfield also has predominantly investigated PX for male participants, which may have introduced bias into results. This paper presents the first literature review on how asymmetric game design is thus far being leveraged in multiplayer VR.…”
Section: Limitationsmentioning
confidence: 96%
“…In future work, we will explore commercial asymmetric VR games as well. Additionally, limitations of our thematic findings are bound to the limitations of the reviewed papers-for example, as also found in general VR research (Peck et al, 2020;MacArthur et al, 2021), this subfield also has predominantly investigated PX for male participants, which may have introduced bias into results. This paper presents the first literature review on how asymmetric game design is thus far being leveraged in multiplayer VR.…”
Section: Limitationsmentioning
confidence: 96%
“…This returned seven unique papers, five of which considered the relationship between gender and cybersickness and were thus included. One other paper was added by hand for a total of six included papers [17,18,29,35,38,47]. This section summarizes and contextualizes the equivocal findings of those papers and concludes that women do experience greater cybersickness than men, but that the size of the gender effect is modest.…”
Section: Is Cybersickness Related To Gender?mentioning
confidence: 96%
“…Two recent systematic reviews [17,47] determined that it is premature to draw conclusions about the relationship between gender and cybersickness. Another systematic review [29] proposed best practices for research on gender differences in cybersickness based on a review of research methods employed in the literature, but the paper stops short of summarizing the existing evidence and therefore does not weigh in on the question of whether gender relates to cybersickness. Two meta-analyses [35,38] approached the question by correlating the proportion of women among participants in each study with overall cybersickness reported by the study, which allows for analysis of papers that do not separately report cybersickness data for men and women.…”
Section: Is Cybersickness Related To Gender?mentioning
confidence: 99%
“…When existing systematic reviews at CHI cite a guideline for their method, they primarily reference PRISMA [63] (e.g., [7,39,51]). The PRISMA figure, specifically, is popular, as it can be a great way to illustrate the search and screening process.…”
Section: Charting a New Trajectory: Critical Issues And Provocationsmentioning
confidence: 99%